(untitled) (Journal of University of Babylon for Engineering Sciences, 2024)
This study aims to calculate the Risk of organochlorine pesticides on the environment residues in the surface waters of Al- Diwaniyah River. Three organochlorine pesticides were targeted (4,4′-DDT, heptachlor, and endosulfan). Ten samples were taken during the pesticide application period from the beginning, middle, and end of the river in the October, the air temperature was 40 degrees Celsius, and the samples were analyzed using Gas chromatography device and the concentration of 4,4′-DDT was from (0.02-0.06 µg/L), heptachlor was from (0.34-0.59 µg/L) and endosulfan was from (0.002-0.03 µg/L). Using the risk quotient method, the ecological risk of these pesticides was calculated, 4,4′-DDT was classified as low risk 0.01≤RQ<0.1. the RQ value was (1.707-3.414 %), for endosulfan was (0.001-0.0327%) and this classified as very low risk RQ <0.01, for heptachlor was (45.977-61.56%), and this classified as moderate risk 0.1≤RQ<1. The study’s findings show that agricultural practices contribute to increasing the concentrations of organochlorine pesticides in river water, thus increasing the ecological risks of these substances and their impact on the public health of living organisms.